Unit Pemerintahan Desa Palsu Pada Sistem Administrasi Negara Indonesia: Pemerintahan Desa, Sistem Administrasi, Indonesia - Budiar (JAMAK: Jurnal Administrasi Manajemen dan Kepemimpinan, 2020)
Local government in Indonesia consists of two levels, namely provincial and district/city. Under the district/city there is the Village Government. Initially, the status of the Village Government was under Law 19/1965 deleted. Then Law 5/1979 formed a new model of village governance that developed through Law 32/2014. Looking at the perspective of state administration, the new model raises the question: whether it is an autonomous region, an administrative area, a non-governmental organization, or a community. To answer these questions, writing is done using a qualitative approach. Data is collected through literature and literature review, as well as document review. The data collected was analyzed descriptively qualitatively. This writing found that Jabon Mekar Village is an institution that is between community institutions and government agencies. Thus, the Village Government in the Indonesian government’s bureaucratic system is a "pseudo government unit" or "fake government unit". Abstrak Pemerintahan daerah di Indonesia terdiri atas dua tingkatan yakni provinsi dan kabupaten/kota. Di bawah kabupaten/kota terdapat Pemerintahan Desa. Awalnya, status Pemerintahan Desa di bawah UU No. 19/ 1965 dihapus. Kemudian UU No. 5/ 1979 membentuk sebuah model pemerintahan desa baru yang berkembang sampai kepada UU No. 32/2014. Ditengok dalam perspektif administrasi negara, model baru tersebut memunculkan pertanyaan: apakah ia merupakan daerah otonom, wilayah administrasi, organisasi nonpemerintah, atau komunitas. Untuk menjawab pertanyaan tersebut dilakukan penulisan menggunakan pendekatan kualitatif. Data dikumpulkan melalui kajian pustaka dan literatur, serta kajian dokumen. Data yang terkumpul dianalisis secara deskriptif kualitatif. Penulisan ini menemukan bahwa Desa Jabon Mekar adalah lembaga yang berada di antara lembaga masyarakat dan lembaga pemerintah. Dengan demikian, Pemerintahan Desa dalam sistem birokrasi pemerintah Indonesia adalah “pseudo government unit” atau “unit pemerintahan palsu”.